Serum glucose, albumin and total protein levels in camels infected with Trypanosoma evansi in Nyala area (Journal of Veterinary Medicine and Animal Production, 2021)
Trypanosomosis caused by Trypanosoma evansiconstitutes serious and economically importantinfections in camels in Sudan and elsewhere. Theparasite is transmitted by biting flies such asTabanus and Stomoxys spp.